Effectiveness of Scramble to the Students’ Reading Comprehension - Lailiyatul Fitriyah (JEET, Journal of English Education and Technology, 2025)
The purpose of the research are to know the influence of teaching reading by using scramble technique on reading comprehension skill of junior high school, to know what extent the influence of teaching reading by using scramble to the student’s reading comprehension skill of junior high school, and to know how the students’ response towards the using Scramble to students’ reading comprehension skill of junior high school. The sample for this research is the eighth grade students of SMP Al-Qon GKB Gresik. The research design is quasi-experimental designs. The writer used test and questionnaire sheet. The test consisted of the pre-test and post-test. The technique to analyze the test is resulted from the students’ scores and calculated by using ANCOVA (Analysis of Covariance). For, questionnaire, the researcher uses Likert scale to know the students’ responses. he result shows that F-value statistical calculation is 12, 95 and in F-table are 4, 02 for d.f 55. So, it shows that there is any influence of teaching reading by using scramble to the students’ reading comprehension skill at the eighth grade students’ of SMP Islamic Qon GKB. The result of the student’s responses is 76% which categorized as “good”. So it can be said that Scramble to the students reading comprehension at the eighth grade students of SMP Islamic Qon GKB is effective.